The 5'-leader sequence of tobacco mosaic virus RNA enhances the expression of foreign gene transcripts in vitro and in vivo. - Gallie, D R (Nucleic Acids Res, 1987)
A 67-nucleotide portion of the non-coding, 5'-leader sequence of tobacco mosaic virus RNA [defined as omega' (Gr. omega prime)] has been shown to enhance the translation of contiguous foreign gene transcripts both in vitro and in vivo. Chemically-synthesized omega', containing convenient linker sequences, was inserted into derivatives of an in vitro transcription plasmid (pSP64) between the bacteriophage-SP6 promoter and sequences coding for either chloramphenicol acetyltransferase (CAT) or neomycin phosphotransferase (NPTII). Run-off in vitro transcripts, with or without a 5'-cap structure (G(5')ppp(5')G) and/or the omega' sequence, were tested in mRNA-dependent cell-free translation systems derived from rabbit reticulocyte lysate, wheat germ extract or Escherichia coli (MRE 600). In all cases, the presence of omega' increased the translational expression of both reporter genes, typically between 2- to 10-fold. Electroporation of isolated mesophyll protoplasts from Nicotiana tabacum cv. Xanthi, or microinjection of oocytes from Xenopus laevis, with SP6-transcripts containing the CAT-coding region confirmed and extended the value of omega' as a potential translational enhancer of gene expression in vivo. IMAGES: